A három prágai egyezmény. Cseh centralizációs törekvések a második világháború utáni Csehszlovákiában - Spišák, Mónika (Közép-Európai Közlemények, 2011)
The status of Slovakia was the main question in liberated postwar Czechoslovakia. The so-called Košice government program adopted on 5 April 1945 denominated the Slovaks „a nationally sovereign nation” but the division of powers between Slovak National Council and the central government was not clear. The first Prague Agreement in 1945 declared that the national organ in Slovakia is the Slovak National Council with a Board of Commissions as its executive body. As a result of the elections in 1946 the Democratic Party had a clear majority in Slovakia but in the czech lands the Communists obtained 41% of the votes. After the elections the main goal of the central government and the Slovak Communist Party became the limitation of Slovak autonomous rights. The result was the second and the third agreement. These documents finally reduced slovak institutions to regional administrative unit of the Prague government.